PENANGGULANGAN KECELAKAAN PENYEBERANGAN KERETA API DI JALAN RUMAH TUMBUH MUARA ENIM DALAM PERSPEKTIF HUKUM PIDANA ISLAM - Lasmini, Lasmini; Tamudin, M (Tazir, 2024)
The frequent occurrence of accidents at railway crossings requires government policy, in this case preventative response, considering that this concerns the lives of other people who must be saved in accordance with the government's duty to protect the entire Indonesian nation and all of Indonesia's bloodshed. Therefore, the researcher considers the need for this research as follows: Handling train crossing accidents on Jalan Rumah Grow Muara Enim from the perspective of Islamic Criminal Law, with two problem formulations, namely, handling train crossing accidents on Jalan Rumah Growing Muara Enim, from an Islamic Criminal Law perspective. towards overcoming train accidents on Jalan Rumah Growing Muara Enim. The research method uses field research. This research was carried out by researching directly at the location to get correct information about what happened at the railroad crossing on Jalan Rumah Grow. The results of this research are that handling accidents at train crossings in Islamic Criminal Law and PT Kereta Api Indonesia both use preventive measures, meaning taking precautions before an accident occurs by instilling discipline (obeying regulations), because regulations are made by the government for problems. People must follow this especially when driving to maintain the safety of their lives. Keywords: Accident Management, Train Crossing, Islamic Criminal Law.